Tratamento da pedofilia para um combate eficiente aos crimes sexuais contra vulneráveis: possibilidades, implantação, exemplos concretos e propostas - Ana Helena German Drumond (2022)
This work aims at stablishing the importance of implementing treatment policies for pedophiles, enabling them to control their sexual impulses and not become criminals. Therefore, in the four chapters that compose this dissertation, the technical aspects of pedophilia are presented, endorsing the difference between pedophiles and sex offenders. The stigma of pedophilia and its relationship with the scarcity of policies for the treatment of the disorder is analyzed, and the main methods of treatment of this paraphilia currently used in the world are evaluated. Subsequently and at last, concrete examples of pedophilia treatment programs already implemented around the world are described and analyzed. As a conclusion, this work points out that, so far, there is no current program or project in the world that can be considered ideal. Despite pedophilia being a frequently studied topic, there is still a lack of reliable studies that allow the safe development of a treatment protocol with proven efficacy. However, it is possible to outline some important considerations and guidelines to the elaboration of such a protocol: (i) the demand of professional assistance by people with pedophilia is real and the wide dissemination of the programs, through various media vehicles, is an effective means of reaching the target audience; (ii) the treatment program must be voluntary and access must be broad and free; (iii) the treatment, in addition to being confidential, must consist of psychotherapy – preferably in groups – combined with the use of medication, according to the individual needs of each patient; (iv) professionals working in the program must keep detailed and up-to-date records of the pedophilia symptoms experienced by patients during treatment, thus allowing the assessment of the effectiveness of the methods used and the eventual need for adaptations.